HUBUNGAN ANTARA ASUPAN MIRONUTRIEN DAN RISIKO TERJADINYA PENYAKIT JANTUNG KORONER PADA POPULASI URBAN DI KOTA MEDAN (LP2MTBM MAKARIOZ, 2023)
There are still 315 people and in 2022 as many as 335 people with coronary heart disease and become patients at the hospital, which is an increase from 2021. This situation indicates that the people of Medan City are prone to coronary heart disease, where the lifestyle of some people from the upper middle class group still consumes food intake that is high in fat and heavy nutrition, and there are still those who do not consume food intake that contains micronutrients or contains nutrients that are good for the body, as well as light nutrition. Therefore, the right thing or policy is needed for the Ministry of Health, especially the Medan City Government in overcoming and reducing coronary heart disease through educational activities so that the public is aware of the dangers of coronary heart. The purpose of this study is to evaluate how the consumption of food intake containing micronutrients is able to reduce obesity rates, and prevent coronary heart disease for people in Medan City. This study used analytical descriptive method with cross sectional approach. Based on the results of research that has been put forward that heart health is caused by age factors and unhealthy habits or diets, where some people as coronary heart disease patients state that coronary heart disease appears at the age of 50-59, and carry out unhealthy food consumption patterns, so that foods that have micronutrients that are little fat and low in nutrients are needed.